Volatile Flavor Compounds Produced by Molds of Aspergillus, Penicillium, and Fungi imperfecti - Kaminski, E. (1974)
Strains of molds Aspergillus niger, A. ochraceus, A. oryzae, A. parasiticus, Penicillium chrysogenum, P. citrinum, P. funiculosum, P. raistrickii, P. viridicatum, Alternaria, Cephalosporium, and Fusarium sp. were grown on sterile coarse wheat meal at 26 to 28 C for 120 h. The volatiles from mature cultures were distilled at low temperature under reduced pressure. The distillates from traps -40 and -78 C were extracted with methylene chloride and subsequently concentrated. All the concentrates thus obtained were analyzed by gas-liquid chromatography, mass spectrometry, chemical reactions of functional groups, and olfactory evaluation. Six components detected in the culture distillates were identified positively: 3-methylbutanol, 3-octanone, 3-octanol, 1-octen-3-ol, 1-octanol, and 2-octen-1-ol. They represented 67 to 97% of all the volatiles occurring in the concentrated distillate. The following 14 components were identified tentatively: octane, isobutyl alcohol, butyl alcohol, butyl acetate, amyl acetate, octyl acetate, pyridine, hexanol, nonanone, dimethylpyrazine, tetramethylpyrazine, benzaldehyde, propylbenzene, and phenethyl alcohol. Among the volatiles produced by molds, 1-octen-3-ol yielding a characteristic fungal odor was found predominant.